Mental health with COVID-19: Health crisis intervention - Maullasari, Sri; Fiana, Anis Lud (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
Purpose - The research objective is to describe and explain health crisis interventions in mental health with COVID-19.Method - This peper use a literature study of various literature on mental health with COVID-19: health crisis interventions.Result - This study indicates that crisis intervention assists those afflicted by a crisis that requires quick handling to be resolved immediately, and the psychological balance is immediately restored during the COVID-19 pandemic.Implications - This research is expected to be the basis for determining intervention models in mental health disorders.Originality - A concept of health crisis intervention assistance.